Bite Forces and Their Measurement in Dogs and Cats - Kim, Se Eun; Arzi, Boaz; Garcia, Tanya C.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2018)
Bite force is generated by interaction of the masticatory muscles, the mandibles and maxillae, the temporomandibular joints (TMJ), and the teeth. Several methods to measure bite forces in dogs and cats have been described. Direct in-vivo measurement of a bite in dogs has been done, however, bite forces were highly variable due to animal volition, situation, or specific measurement technique. Bite force has been measured in-vivo from anesthetized dogs by electrical stimulation of jaw adductor muscles, but this may not be reflective of volitional bite force during natural activity. In-vitro bite forces have been estimated by calculation of the force produced using mechanical equations representing the jaw adductor muscles, and of the mandible and skull structure Bite force can be estimated in-silico using finite element analysis (FEA) of the computed model of the anatomical structures. FEA can estimate bite force in extinct species, however, estimates may be lower than the measurements in live animals and would have to be validated specifically in domestic dogs and cats to be reliable. The main factors affecting the bite forces in dogs and cats are body weight and the skull’s morphology and size. Other factors such as oral pain, TMJ disorders, masticatory muscle atrophy, and malocclusion may also affect bite force. Knowledge of bite forces in dogs and cats is essential for various clinical and research fields such as the development of implants, materials, and surgical techniques as well as for forensic medicine. This paper is a summary of current knowledge of bite forces in dogs and cats, including the effect of measurement methods and of other factors .